Bio-based carbon foam phase change energy storage material and preparation method and application thereof
By adopting biological base foam charcoal -phase transformation energy storage materials, using catalytic liquefaction and molecular reconstruction technology to prepare high -heat -conducting and high -heat storage materials to solve the problem of low heat management efficiency of photovoltaic components, realize the efficiency of photovoltaic power generation Improvement and improvement of material safety.
Patent Information
- Application Number
- CN202410472839.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-04-18
AI Technical Summary
The thermal management efficiency of existing photovoltaic modules is low, resulting in a decrease in power generation efficiency and shortened life. Traditional insulation foam materials are flammable and have low thermal conductivity, making it difficult to quickly transfer and absorb heat.
Using biological biological bubble charcoal phase transformation energy storage materials, through catalytic liquefaction, molecular reconstruction, foaming and carbonization technologies, prepare materials with uniform structure, heat conduction, and good thermal storage performance, and improve the material through vacuum impregnation and coating process. Load rate and mechanical performance.
The efficient heat transfer and storage have been realized, and the efficiency of photovoltaic power generation has been improved. Compared with conventional insulation layers of material power generation efficiency, it can increase the efficiency of 12 % to 15 %, and solve the problem of flammable and low thermal guidance.
Smart Images

Figure CN118389126B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage materials, and in particular to a bio-based foam carbon phase change energy storage material and a preparation method and application thereof. Background Art
[0002] Building integrated photovoltaic (BIPV) is a technology that integrates solar power generation (photovoltaic) products into buildings. It integrates photovoltaic systems into buildings as part of building components and assumes building functions, such as photovoltaic tiles and photovoltaic walls. BIPV can replace traditional enclosure structures, reduce the cooling and heating loads of buildings, and generate electricity to supply electricity for daily operation of buildings, thereby reducing the overall energy consumption of buildings. However, up to now, the actual photoelectric conversion efficiency of general photovoltaic modules is not high. More than 80% of the solar radiation energy received by the surface of photovoltaic modules is converted into heat, part of which is dissipated into the surrounding environment, and most of it is converted into the internal energy of the battery, which raises the temperature of the photovoltaic cell to about 40°C higher than the ambient temperature. As the internal energy of the photovoltaic cell increases, its temperature gradually rises, which leads to a gradual decrease in photoelectric efficiency. In addition, excessive temperature will greatly shorten the life of the photovoltaic cell. Therefore, it is necessary to evacuate the heat of the components in time to improve the power generation efficiency. There are various cooling methods for photovoltaic modules, and the most widely used are air cooling and water cooling, but additional cooling channels are required, which increases the complexity of the photovoltaic system.
[0003] Phase change materials (PCM) absorb or release a large amount of latent heat of phase change by converting between liquid and solid in a very narrow temperature range, and can be used to absorb heat from photovoltaic modules. When the system is working during the day, it absorbs excess heat and melts to keep the photovoltaic panels at the optimal operating temperature, thereby increasing the total power generation of the system. When the temperature drops at night, the phase change material solidifies and releases heat, which can also prevent the system from being damaged due to excessive temperature differences in seasons with large temperature differences. Foam materials are often used as wall insulation materials for urban buildings because of their low apparent density and thermal conductivity. Therefore, foam materials and phase change materials are combined and used in photovoltaic walls, which can not only serve as the insulation layer of the building, but also absorb the heat generated by photovoltaic power generation and improve power generation efficiency.
[0004] Although traditional thermal insulation foam materials have excellent insulation and mechanical properties, they are flammable and produce irritating toxic gases when burned. Phenolic foam with excellent flame retardant properties has become the best alternative. Phenolic foam is prepared by foaming phenolic resin, but its important raw material, phenol, is a non-renewable petrochemical product. Therefore, replacing phenol with biomass raw materials has become a research hotspot, but bio-based foam phase change composite materials still have the problem of low thermal conductivity. How to improve thermal conductivity so that heat can be quickly transferred and absorbed is also one of the problems that need to be solved urgently.
[0005] Publication number CN115247049A discloses a method for preparing a graphite foam-based phase change energy storage material, wherein polyurethane foam is soaked in a sodium hydroxide solution, the pretreated polyurethane foam is soaked in a phenolic resin-graphite solution, dried, cured and sintered to prepare graphite foam, and an organic phase change material is filled into the graphite foam to obtain a graphite foam-based phase change energy storage material. The graphite foam-based phase change energy storage material has good heat storage performance and good anti-leakage performance, but its thermal conductivity is low, so the heat transfer efficiency of the phase change energy storage material used alone in the energy storage system is low, which greatly limits its application in practice. Summary of the invention
[0006] The present invention aims to provide a bio-based carbon foam phase change energy storage material and its preparation method and application. The present invention uses renewable and sustainable biomass energy as raw material, and prepares a bio-based carbon foam phase change energy storage material with uniform structure, good thermal conductivity and heat storage performance through catalytic liquefaction, molecular reconstruction, induced foaming and carbonization, vacuum impregnation and other technologies.
[0007] To achieve the above object, the present invention provides a method for preparing a bio-based carbon foam phase change energy storage material, comprising:
[0008] The bio-based raw material and phenol are uniformly mixed, reacted at 120-150° C. for 30-120 minutes with acid as catalyst, NaOH is added to adjust the pH value to neutral, and the temperature is reduced to 30-40° C. to obtain a bio-based liquefied product;
[0009] The bio-based liquefied product, 40% sodium hydroxide solution and paraformaldehyde are mixed uniformly, heated to 75-90° C., reacted for 30-60 minutes, cooled to below 40° C., and a hydrochloric acid solution is added to adjust the pH value to neutral to obtain a bio-based liquefied synthetic product;
[0010] The bio-based liquefied synthetic product, a nucleating agent, a surfactant, a foaming agent and a curing agent are uniformly mixed, and foamed at 70 to 80° C. for 40 to 60 minutes to obtain a bio-based foam material, and the bio-based foam material is carbonized at 800 to 1000° C. for 2 to 4 hours under nitrogen protection to obtain a bio-based foam carbon material;
[0011] The phase change matrix with a phase change temperature of 40°C to 50°C is heated until it melts, a bio-based foam carbon material is added, and vacuum impregnation is performed for 1 to 2 hours, and the impregnation is performed 2 to 3 times to obtain a bio-based foam carbon phase change composite material;
[0012] A phase change matrix with a phase change temperature of 20° C. to 35° C. and a thermal conductive adhesive are uniformly mixed and then coated on a bio-based carbon foam phase change composite material to obtain a bio-based carbon foam phase change energy storage material.
[0013] Preferably, the mass ratio of the bio-based raw material to phenol is 1:(2-3).
[0014] Preferably, the bio-based raw material is any one or more of wood powder, peanut shell powder, walnut shell powder and bamboo powder.
[0015] Preferably, the acid is any one or more of an inorganic medium strong acid and an organic strong acid, such as sulfuric acid, hydrochloric acid, phosphoric acid, formic acid and oxalic acid.
[0016] Preferably, the mass ratio of the bio-based liquefied material, 40% sodium hydroxide solution and paraformaldehyde is 1:(0.1-0.3):(0.3-0.5).
[0017] Preferably, the solid content of the bio-based liquefied synthetic product is 60% to 65%.
[0018] Preferably, the mass ratio of the bio-based liquefied synthetic product, the nucleating agent, the surfactant, the foaming agent and the curing agent is 1:(0.1-0.2):(0.04-0.08):(0.1-0.15):(0.1-0.2).
[0019] Preferably, the nucleating agent is a solid metal chloride, and the solid metal chloride is any one or more of zinc chloride, copper chloride, and magnesium chloride.
[0020] Preferably, the surfactant is a nonionic surfactant, and the nonionic surfactant is any one or more of Tweens and polyoxyethylene castor oils.
[0021] Preferably, the foaming agent is an alkane with a boiling point less than 70° C., and the alkane with a boiling point less than 70° C. is any one or more of n-pentane and n-hexane.
[0022] Preferably, the curing agent is a composite curing agent mixed with a strong acid and a weak acid, the strong acid is any one of hydrochloric acid and p-toluenesulfonic acid, and the weak acid is any one of formic acid, phosphoric acid, and sulfurous acid.
[0023] Preferably, the phase change matrix with a phase change temperature of 40°C to 50°C is any one or more of polyethylene glycol 1500, docosane, and tetracosane; the phase change matrix with a phase change temperature of 20°C to 35°C is any one or more of polyethylene glycol 800, hexadecane, and octadecane.
[0024] Preferably, the mass ratio of the phase change matrix with a phase change temperature of 20° C. to 35° C. to the thermal conductive adhesive is (0.8-1.2):1.
[0025] Preferably, the thermally conductive adhesive is any one or more of epoxy resin thermally conductive adhesive, acrylic thermally conductive adhesive, and polyurethane thermally conductive adhesive.
[0026] The present invention also provides a bio-based foam carbon phase change energy storage material, which is prepared by the above-mentioned preparation method.
[0027] The present invention also provides an application of a bio-based foam carbon phase change energy storage material in a photovoltaic wall.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] 1. The present invention uses biomass energy as raw material, adopts phenol as liquefaction agent, obtains bio-based liquefied product through acid catalysis, transforms the original low-activity biomass polymer into high-activity biomass polymer, and then undergoes molecular reconstruction with sodium hydroxide solution and paraformaldehyde to obtain bio-based liquefied synthetic product. The synthetic product obtains bio-based foamed carbon material after inducing foaming and carbonization. The bio-based foamed carbon material is added to the melted phase change matrix, and after vacuum impregnation, a bio-based foamed carbon phase change energy storage material with uniform structure, good thermal conductivity and heat storage performance is obtained.
[0030] 2. The present invention adopts paraformaldehyde to replace the traditional formaldehyde solution for reaction. Since the solid content of traditional formaldehyde is 37%, the solid content of the product synthesized with liquefied resin is low and needs to be dehydrated before foaming. By adopting paraformaldehyde, a high-solid foaming precursor can be prepared by optimizing the feed ratio, reaction temperature and reaction time, without the cumbersome process of later dehydration, saving production energy consumption and time.
[0031] 3. The present invention adds solid metal compounds as foaming nucleating agents, which is beneficial to heterogeneous nucleation, can increase the cell density, make the pore structure of the formed foam more delicate and uniform, and form a foam material with uniform structure, small pore size, high density and high strength. The thermal conductivity of the foam material is improved by mixing and foaming the metal compounds, and the efficient absorption and conversion between thermal energy and chemical energy is achieved.
[0032] 4. When loading the phase change energy storage material, the core layer of the present invention adopts vacuum impregnation and the surface layer adopts coating process. The phase change matrix and the thermal conductive adhesive are mixed and then coated, which greatly increases the loading rate of the phase change energy storage material, improves the heat absorption capacity of the phase change energy storage material, improves its mechanical properties, and solves the problem of phase change matrix leakage.
[0033] 5. The bio-based foam carbon phase change energy storage material prepared by the present invention has an energy storage efficiency of 99.5% to 100%, and a thermal conductivity of 107 to 125 W / m·K. When applied to photovoltaic walls, the working heat of the photovoltaic panels can be transferred and stored in time when the photovoltaic panels are working, which can reduce the working temperature of the photovoltaic panels and improve the power generation efficiency. Compared with conventional insulation materials, the power generation efficiency can be increased by 12% to 15%. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1is a scanning electron microscope photograph of the bio-based foam carbon material prepared in Example 1;
[0035] Figure 2 It is a schematic diagram of the structure of the bio-based foam carbon phase change energy storage material prepared in Example 1.
[0036] Among them: 1. core layer phase change material, 2. core layer foam carbon material, 3. phase change-thermal conductive composite material. DETAILED DESCRIPTION
[0037] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0038] The main compounds used in the examples and comparative examples and their sources are as follows:
[0039] Table 1 Materials and sources
[0040]
[0041]
[0042] Example 1
[0043] A method for preparing a bio-based carbon foam phase change energy storage material comprises the following steps:
[0044] (1) Bamboo powder and phenol were mixed uniformly in a mass ratio of 1:2, and hydrochloric acid was used as a catalyst, and the mixture was reacted at 135° C. for 80 min. NaOH solution was added to adjust the pH value to neutral, and the temperature was lowered to 30° C. to obtain a bio-based liquefied product.
[0045] (2) The bio-based liquefied product, 40% sodium hydroxide solution and polyformaldehyde were mixed uniformly in a mass ratio of 1:0.2:0.4, heated to 80° C., reacted for 40 minutes, and cooled to below 40° C. to obtain a bio-based liquefied synthetic product with a solid content of 65%.
[0046] (3) The bio-based liquefied synthetic product, zinc chloride, Tween 80, n-hexane, and a mixed solution of hydrochloric acid and p-toluenesulfonic acid are uniformly mixed in a mass ratio of 1:0.12:0.08:0.12:0.18, and foamed at 80°C for 50 minutes to obtain a bio-based foam material.
[0047] (4) The bio-based foam material was carbonized at 900°C for 2 h to obtain a bio-based carbon foam material. The bio-based carbon foam material was observed using a scanning electron microscope. The results are as follows: Figure 1 As shown, it can be seen that the pore size distribution of the foam carbon material is uniform, ranging from 80 to 120 microns, the pore structure is complete, and it has a certain open porosity, and can be impregnated with phase change materials.
[0048] (5) Heat docosane until it is melted, add the bio-based carbon foam material, and perform vacuum impregnation for 2 hours, and perform the impregnation twice to obtain a bio-based carbon foam phase change composite material.
[0049] (6) Polyethylene glycol 800 and polyurethane thermal conductive adhesive are mixed evenly in a mass ratio of 1:1, and then coated on the bio-based carbon foam phase change composite material to obtain a bio-based carbon foam phase change energy storage material. The structural schematic diagram of the material is shown in FIG. Figure 2 As shown, it is divided into two parts, the surface layer and the core layer. The surface layer is a phase change-thermal conductive composite material 3, which is a mixture of polyethylene glycol 800 and polyurethane thermal conductive adhesive. The core layer includes a core layer phase change material 1 and a bio-based foam carbon material 2. The core layer phase change material 1 is docosane.
[0050] Example 2
[0051] A method for preparing a bio-based carbon foam phase change energy storage material comprises the following steps:
[0052] (1) Peanut shell powder and phenol were mixed uniformly in a mass ratio of 1:2.5, and sulfuric acid was used as a catalyst. The mixture was reacted at 125° C. for 70 min, and a NaOH solution was added to adjust the pH value to neutral. The temperature was lowered to 30° C. to obtain a bio-based liquefied product.
[0053] (2) The bio-based liquefied product, 40% sodium hydroxide solution and polyformaldehyde were mixed uniformly in a mass ratio of 1:0.1:0.3, heated to 85° C., reacted for 50 minutes, and cooled to below 40° C. to obtain a bio-based liquefied synthetic product with a solid content of 65%.
[0054] (3) The bio-based liquefied synthetic product, copper chloride, polyoxyethylene castor oil, n-pentane, and a mixed solution of formic acid and p-toluenesulfonic acid are uniformly mixed in a mass ratio of 1:0.16:0.06:0.1:0.15, and foamed at 70°C for 45 minutes to obtain a bio-based foam material.
[0055] (4) The bio-based foam material is carbonized at 800°C for 3 hours to obtain a bio-based foam carbon material.
[0056] (5) Polyethylene glycol 1500 is heated until it is melted, and a bio-based carbon foam material is added thereto. The mixture is vacuum impregnated for 1 hour, and the impregnation is repeated three times to obtain a bio-based carbon foam phase change composite material.
[0057] (6) Octadecane and epoxy resin thermal conductive adhesive are mixed evenly at a mass ratio of 0.9:1, and then coated on the bio-based carbon foam phase change composite material to obtain a bio-based carbon foam phase change energy storage material.
[0058] Example 3
[0059] A method for preparing a bio-based carbon foam phase change energy storage material comprises the following steps:
[0060] (1) Poplar wood powder and phenol were uniformly mixed in a mass ratio of 1:2, oxalic acid was used as a catalyst, the mixture was reacted at 140° C. for 120 min, a NaOH solution was added to adjust the pH value to neutral, and the temperature was reduced to 30° C. to obtain a bio-based liquefied product.
[0061] (2) The bio-based liquefied product, 40% sodium hydroxide solution and polyformaldehyde were mixed uniformly in a mass ratio of 1:0.3:0.5, heated to 90° C., reacted for 30 minutes, and cooled to below 40° C. to obtain a bio-based liquefied synthetic product with a solid content of 64%.
[0062] (3) The bio-based liquefied synthetic product, magnesium chloride, polyoxyethylene castor oil, n-hexane, and a mixed solution of hydrochloric acid and sulfurous acid are uniformly mixed in a mass ratio of 1:0.1:0.04:0.13:0.17, and foamed at 80° C. for 55 minutes to obtain a bio-based foam material.
[0063] (4) The bio-based foam material is carbonized at 1000°C for 2 hours to obtain a bio-based foam carbon material.
[0064] (5) Tetracosane is heated until it is melted, and a bio-based carbon foam material is added, and vacuum impregnation is performed for 1.5 hours, and the impregnation is performed three times to obtain a bio-based carbon foam phase change composite material.
[0065] (6) Hexadecane and acrylic thermal conductive adhesive are mixed evenly in a mass ratio of 1.1:1, and then coated on a bio-based carbon foam phase change composite material to obtain a bio-based carbon foam phase change energy storage material.
[0066] Comparative Example 1
[0067] A method for preparing a bio-based foam phase change energy storage material comprises the following steps:
[0068] (1) Poplar wood powder and phenol were uniformly mixed in a mass ratio of 1:2, oxalic acid was used as a catalyst, the mixture was reacted at 140° C. for 120 min, a NaOH solution was added to adjust the pH value to neutral, and the temperature was reduced to 30° C. to obtain a bio-based liquefied product.
[0069] (2) The bio-based liquefied product, 40% sodium hydroxide solution and polyformaldehyde were mixed uniformly in a mass ratio of 1:0.3:0.5, heated to 90° C., reacted for 30 minutes, and cooled to below 40° C. to obtain a bio-based liquefied synthetic product with a solid content of 64%.
[0070] (3) The bio-based liquefied synthetic product, magnesium chloride, polyoxyethylene castor oil, n-hexane, and a mixed solution of hydrochloric acid and sulfurous acid are uniformly mixed in a mass ratio of 1:0.1:0.04:0.13:0.17, and foamed at 80° C. for 55 minutes to obtain a bio-based foam material.
[0071] (4) Tetracosane is heated until it melts, and the bio-based foam material is added, and the mixture is vacuum impregnated for 1.5 hours, and the impregnation is repeated three times to obtain a bio-based foam phase change composite material.
[0072] (5) Hexadecane and acrylic thermal conductive adhesive are mixed evenly in a mass ratio of 1.1:1, and then coated on a bio-based foam phase change composite material to obtain a bio-based foam phase change energy storage material.
[0073] Comparative Example 2
[0074] A method for preparing a bio-based carbon foam phase change energy storage material, which is different from Example 3 in that magnesium chloride is not added in step (3).
[0075] Performance Testing
[0076] Heat storage efficiency test: The dynamic heat flow meter method is used to measure the latent heat of phase change of the phase change composite materials in Examples 1 to 3 and Comparative Examples 1 to 2. The ratio of the latent heat of phase change of the phase change composite materials in Examples 1 to 3 and Comparative Examples 1 to 2 is the heat storage efficiency.
[0077] Thermal conductivity test: The phase change energy storage materials in Examples 1 to 3 and Comparative Examples 1 to 2 were tested according to the thermal conductivity test method in GBT 10294-2008.
[0078] Compression strength test: The compression strength of the phase change energy storage materials in Examples 1 to 3 and Comparative Examples 1 to 2 was tested according to the standard for determining the compression properties of rigid foam plastics in GBT 8813-2020.
[0079] Table 2 Phase change energy storage material performance test results
[0080]
[0081]
[0082] As can be seen from Table 2, the heat storage efficiency, thermal conductivity and compressive strength of the phase change energy storage materials prepared in Examples 1 to 3 are higher than those prepared in Comparative Examples 1 to 2. Compared with Example 3, Comparative Example 1 did not carbonize the foam material, and the carbonized foam material can form a graphite crystal structure. At the same time, this process is also conducive to the reduction of impurities and defects, so that heat energy can be transmitted more efficiently, so the heat storage efficiency, thermal conductivity and compressive strength of the corresponding material can be effectively improved. Compared with Example 3, Comparative Example 2 did not add the metal compound magnesium chloride during the foaming process, and the metal ions not only have a high heat transfer efficiency, but also can promote the carbonization process of the foam. The addition of metal ions is also conducive to the heterogeneous nucleation of the foam, which can increase the pore density and foam strength. Therefore, the heat storage efficiency, thermal conductivity and compressive strength of the corresponding material can also be effectively improved.
[0083] Application Example 1
[0084] The photovoltaic panels were respectively combined with the phase change energy storage materials in Examples 1 to 3 and Comparative Examples 1 to 2 to prepare photovoltaic wall samples, and then the rock wool board and the photovoltaic panels were combined to prepare conventional photovoltaic wall samples.
[0085] Performance Testing
[0086] Power generation efficiency improvement test: connect the positive and negative poles of the photovoltaic panel in Application Example 1 to the measuring equipment, measure the current and voltage output when the photovoltaic panel is working normally, and calculate the power generation efficiency of different photovoltaic wall samples. The power generation efficiency improvement in Table 3 refers to the comparison with the conventional photovoltaic wall sample prepared in Application Example 1.
[0087] Table 3 Photovoltaic wall sample performance test results
[0088]
[0089] As can be seen from Table 3, when the phase change energy storage materials prepared in Examples 1 to 3 are applied to photovoltaic walls, the improvement in power generation efficiency is higher. Compared with Example 3, the foam material of Comparative Example 1 did not undergo a carbonization reaction. Compared with the foam material that underwent a carbonization reaction, its thermal conductivity was reduced by about 71%, resulting in the heat generated in the photovoltaic power generation process being unable to be quickly transferred, affecting the power generation efficiency. When the bio-based foam phase change energy storage material prepared in Comparative Example 1 was applied to a photovoltaic wall, the improvement in its power generation efficiency was about 39% lower. Compared with Example 3, when the bio-based foam carbon phase change energy storage material prepared in Comparative Example 2 was applied to a photovoltaic wall, the improvement in its power generation efficiency was also about 28% lower. This is because the metal compound magnesium chloride was not added during the foaming process in Comparative Example 2, and the metal ions not only have a high heat transfer efficiency, but also can promote the carbonization process of the foam. The addition of metal ions is also beneficial to the heterogeneous nucleation of the foam. In addition to improving the pore density, foam strength and thermal conductivity of foam carbon, it can also promote the heat generated during photovoltaic power generation to be quickly transferred in the wall material and absorbed by the phase change matrix, thereby improving the power generation efficiency.
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a bio-based carbon foam phase change energy storage material, characterized in that: include: The bio-based raw material and phenol are uniformly mixed, and an acid is used as a catalyst to react at 120 to 150° C. for 30 to 120 minutes, and a NaOH solution is added to adjust the pH value to neutral, and the temperature is lowered to 30 to 40° C. to obtain a bio-based liquefied product; The bio-based liquefied product, 40% sodium hydroxide solution and paraformaldehyde solution are mixed uniformly, heated to 75-90°C, reacted for 30-60 minutes, cooled to below 40°C, and hydrochloric acid solution is added to adjust the pH value to neutral, thereby obtaining a bio-based liquefied synthetic product; The bio-based liquefied synthetic product, a nucleating agent, a surfactant, a foaming agent and a curing agent are uniformly mixed, and foamed at 70 to 80° C. for 40 to 60 minutes to obtain a bio-based foam material, and the bio-based foam material is carbonized at 800 to 1000° C. under nitrogen protection for 2 to 4 hours to obtain a bio-based foam carbon material; the nucleating agent is a solid metal chloride, and the solid metal chloride is any one or more of zinc chloride, copper chloride and magnesium chloride; The phase change matrix with a phase change temperature of 40°C to 50°C is heated until it melts, a bio-based carbon foam material is added, and the mixture is vacuum impregnated for 1 to 2 hours, and the impregnation is performed 2 to 3 times to obtain a bio-based carbon foam phase change composite material; the phase change matrix with a phase change temperature of 40°C to 50°C is any one or more of polyethylene glycol 1500, docosane, and tetracosane; A phase change matrix with a phase change temperature of 20°C to 35°C and a thermal conductive adhesive are evenly mixed and then coated on a bio-based carbon foam phase change composite material to obtain a bio-based carbon foam phase change energy storage material; the phase change matrix with a phase change temperature of 20°C to 35°C is any one or two of polyethylene glycol 800 and octadecane.
2. The method for preparing a bio-based carbon foam phase change energy storage material according to claim 1, characterized in that: The mass ratio of the bio-based raw material to phenol is 1:(2-3); the bio-based raw material is any one or more of wood powder, peanut shell powder, walnut shell powder, and bamboo powder; and the acid is any one or more of inorganic medium-strong acid and organic strong acid.
3. The method for preparing a bio-based carbon foam phase change energy storage material according to claim 1, characterized in that: The mass ratio of the bio-based liquefied material, 40% sodium hydroxide solution and paraformaldehyde is 1: (0.1-0.3): (0.3-0.5); the solid content of the bio-based liquefied synthetic product is 60%-65%.
4. The method for preparing a bio-based carbon foam phase change energy storage material according to claim 1, characterized in that: The mass ratio of the bio-based liquefied synthetic product, the nucleating agent, the surfactant, the foaming agent and the curing agent is 1: (0.1-0.2): (0.04-0.08): (0.1-0.15): (0.1-0.2).
5. The method for preparing a bio-based carbon foam phase change energy storage material according to claim 1, characterized in that: The surfactant is a nonionic surfactant; the nonionic surfactant is any one or more of Tween and polyoxyethylene castor oil.
6. The method for preparing a bio-based carbon foam phase change energy storage material according to claim 1, characterized in that: The foaming agent is an alkane with a boiling point less than 70° C.; the alkane with a boiling point less than 70° C. is any one or more of n-pentane and n-hexane.
7. The method for preparing a bio-based carbon foam phase change energy storage material according to claim 1, characterized in that: The curing agent is a composite curing agent mixed with a strong acid and a weak acid; the strong acid is any one of hydrochloric acid and p-toluenesulfonic acid; the weak acid is any one of formic acid, phosphoric acid and sulfurous acid.
8. The method for preparing a bio-based carbon foam phase change energy storage material according to claim 1, characterized in that: The mass ratio of the phase change matrix with a phase change temperature of 20°C to 35°C to the thermal conductive adhesive is (0.8-1.2):1; the thermal conductive adhesive is any one or more of epoxy resin thermal conductive adhesive, acrylic thermal conductive adhesive, and polyurethane thermal conductive adhesive.
9. A bio-based carbon foam phase change energy storage material, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. Use of the bio-based carbon foam phase change energy storage material according to claim 9 in photovoltaic walls.
Citation Information
Patent Citations
Graphite foam-based phase change energy storage material and preparation method thereof
CN115247049A
Method for preparing biomass-based foam materials from natural fiber biomass materials
CN103992497A
Foamy carbon / paraffin type phase-change composite material and encapsulation method thereof
CN104893674A